THE EFFECT OF PHYSICAL EXERCISE ON BLOOD SUGAR CONTROL IN DIABETIC PATIENTS - Wang,Weilin (2021)
ABSTRACT Introduction Diabetes is a metabolic disease characterized by hyperglycemia. It is a metabolic syndrome in which blood sugar levels increase due to defects in insulin secretion or impaired function, or even both defects. Object To understand the effect of diabetic patients in controlling blood sugar through physical exercise, the paper analyzes the correlation between the exercise status and physiological indicators of diabetic patients in our hospital. Methods We randomly selected 41 diabetic patients and monitored their exercise. At the same time, we check the physiological indicators of the patients after the exercise is completed and analyze the control of blood sugar by sports. Results After healthy physical exercise, the blood sugar level of diabetic patients tended to stabilize, and the glycosylated hemoglobin level decreased. The blood sugar levels of patients who did not participate in healthy physical exercises were not stable, and their glycosylated hemoglobin levels did not improve. Conclusion Healthy sports is a simple, easy, safe and effective adjuvant therapy for the prevention and treatment of diabetes, and it is worthy of clinical promotion. Level of evidence II; Therapeutic studies - investigation of treatment results.